The Spatiotemporal Dynamics of Heatwaves and Cold‐Spells in Earth's Largest Freshwater Systems - Hazem U. Abdelhady; David Cannon; Ayumi Fujisaki‐Manome; Andrew Gronewold; Jia Wang (Geophysical Research Letters, 2025)
Abstract Extreme water temperatures impact the ecological and economic value of freshwater systems. They disrupt fisheries habitat, trigger harmful algal blooms, and stress coastal infrastructure. This study examines the spatiotemporal patterns of heatwaves and cold‐spells in the Great Lakes using 82 years of simulated surface temperature data. Significant increasing trends in heatwave duration were observed in Lake Superior and Lake Michigan‐Huron, while cold‐spell duration increased on all lakes except Ontario. Temperature anomalies during these events varied from the climatological mean by as much as ±10°C, but did not change significantly over time. Analysis revealed substantial spatial variability in heatwaves and cold‐spells, both within and across lakes, with differences driven by air temperature and ice cover anomalies as well as associated climate teleconnections (i.e., the East Pacific/North Pacific and Atlantic Multidecadal Oscillation). These findings highlight the importance of both climatic and lake processes in shaping extreme temperature events.